Cation exchange mediated elimination of the Fe-antisites in the hydrothermal synthesis of LiFePO4. (September 2015) - Paolella, Andrea; Bertoni, Giovanni; Hovington, Pierre; Feng, Zimin; Flacau, Roxana; Prato, Mirko; Colombo, Massimo; Marras, Sergio; Manna, Liberato; Turner, Stuart; Van Tendeloo, Gustaaf; Guerfi, Abdelbast; et al.
Abstract: In this work we elucidate the elimination of mechanism Fe-antisite defects in lithium iron phosphate (LiFePO4 ) during the hydrothermal synthesis. Compelling evidence of this effect is provided by combining Neutron Powder Diffraction (NPD), High Resolution (Scanning) Transmission Electron Microscopy (HR-(S)TEM), Electron Energy Loss Spectroscopy (EELS), X-Ray Photoelectron Spectroscopy (XPS) and calculations. We found: i) the first intermediate vivianite inevitably creates Fe-antisite defects in LiFePO4 ; ii) the removal of these antisite defects by cation exchange is assisted by a nanometer-thick amorphous layer, rich in Li, that enwraps the LiFePO4 crystals. Graphical abstract: Highlights: Vivianite is responsible of the formation of the Fe-antisites. A nanometer thick amorphous layer promotes a cation exchange reaction that removes the Fe- antisites. The removal of Fe-antisites is proved by Neutron Powder Diffraction and HAADF-STEM.